Pemberdayaan Ekonomi Komunitas Perempuan melalui Pelatihan Penjahitan dan Pemasaran Scrunchie - Ega Gradini; Naluri Yanti; Dina Anggraini; Julis Agustini; Diana Tirmiara; Vina Hidayanti; Riki Temas Miko; Chairul Putra (LSM Catimore dan Sahabat, 2023)
Women's economic empowerment is the capacity of women to participate, contribute, and benefit from the process of economic growth in a way that recognizes the value of contributions and respects the dignity of women. This service activity is in the form of sewing training and marketing scrunchie for the women's community in Rata Ara village, District of Bener Meriah. This service program aims to provide skills and creativity, as well as support women's economic empowerment in Rata Ara village. The activity was carried out for four days involving 28 participants from the women's community in Rata Ara village. The Community Service team is a KKN group of the Islamic State Institute of Takengon. The method used is Direct Instruction. The service activities went well, were effective, and provided skills and creativity to support women's economic empowerment in Rata Ara village. This activity produces products in the form of scrunchies that are packaged economically and then marketed offline and online.